Mineral magnetism records shift in climate during the Kannur regolith formation, North Kerala, India - Linu Babu; Sangode Satish J; Reethu Mohan; R.S. Prasanth; S. Rajesh; Mahesh Mohan; A.P. Pradeepkumar (Quaternary Science Advances, 2023)
In this study, we conducted mineral magnetic analyses on three borehole core samples (∼40 m each) from the Kannur midland of northern Kerala, India to investigate iron oxide variations. Magnetic susceptibility (χlf) and its frequency dependency (χfd), Anhysteretic Remanence Magnetization (ARM), Isothermal Remanence Magnetization (IRM), Saturation IRM (SIRM), Hard IRM (HIRM), Soft IRM, and Munsell-Redness Rating were utilized to identify and estimate the iron oxide variations in these samples. We observed a notable shift from reductive to oxidative environments between 20 and 30 m depths among the studied cores, indicating a significant climatic or tectonic event in the region. This abrupt changeover is consistent with the lithologic change marked by a brief peat interval followed by lateritic sediments, which reflect the anoxic to oxic conditions within the closed system of the Kannur regolith basin. The basin-fill, characterized by the rapid hinterland erosion of upland laterites without the return of peat environments, suggests monsoonal intensification. The widespread occurrence of this interval within the basin may indicate a significant change in the climate. We observed an enrichment of authigenic magnetites in peat and lagoonal clays, which are succeeded by hematite and goethite-dominant estuarine to fluvial conditions inferred for monsoonal intensification during stabilized sea level and tectonic stability in the mid-Holocene. The goethite/hematite magnetic mineral ratio revealed the variation within warm-humid to warm-arid conditions, elaborating the monsoonal variability through the majority of the Mid to Late Holocene in the absence of chronology. We propose that this changeover in authigenic reductive to oxidative detrital magnetic mineralogy can serve as a stratigraphic benchmark for climate change during the Mid to Late Holocene in the Kannur basin of Kerala.